The Association between Helicobacter pylori Infection and Chronic Hepatitis C: A Meta-Analysis and Trial Sequential Analysis - Juan Wang; Wen-Ting Li; Yi-Xiang Zheng; Shu-Shan Zhao; Ning Li; Yan Huang; Rong-Rong Zhou; Ze-Bing Huang; Xue-Gong Fan (Gastroenterology Research and Practice)
Purpose. Helicobacter pylori is a common gastric disease-inducing pathogen. Although an increasing number of recent studies have shown that H. pylori is a risk factor for liver disease, the potential association between H. pylori infection and chronic hepatitis C still remains controversial. The aim of our meta-analysis was to evaluate a potential association between H. pylori infection and chronic hepatitis C. Methods. We searched the PubMed, Embase, CNKI, Web of Science, and the Cochrane Central Register of Controlled Trials (CENTRAL) databases between January 1, 1994, and May 1, 2015. Results. This study included a total of 1449 patients with chronic hepatitis C and 2377 control cases. The prevalence of H. pylori was significantly higher in patients with chronic hepatitis C than in those without chronic hepatitis C. The pooled odds ratio was 2.93. In a subgroup analysis, the odds ratios were 4.48 for hepatitis C virus- (HCV-) related cirrhosis and 5.45 for hepatocellular carcinoma. Conclusion. Our study found a strong association between H. pylori and chronic hepatitis C, particularly during the HCV progression stage; thus, we recommend active screening for H. pylori in patients with chronic hepatitis C.